A Model For Direct Dragline Casting In A Dipping Coal-Seam - B. Erdem (The Southern African Institute of Mining and Metallurgy, 2004)
This article introduces a computer model, which emphasizes panel design for draglines deployed in direct side-casting mode. The study covers flat and inclined coal-seam conditions with the dragline operating along the strike-line. Two casting methods are embedded in the model: material is placed in the open set adjacent to the one on which the dragline is located (the DNS method) and material is placed in the open set adjacent to the one the dragline excavates (the DND method). While in the first method the unproductive walking time is reduced as the set is enlarged, in the second method the cycle time is lessened as the dragline swings along an acute angle. The side-casting model is shaped so as to provide several panel configurations instead of a single one to conform to the characteristics for an opencast mine. This is achieved by assigning the pit width an interval of values ranging from a minimum to a maximum. The model includes solutions to other critical design parameters such as: set length, swing angles at key cut and main cut positions, and required dragline reach at key cut and main cut positions. The model outcomes reveal the following: the stripping operation is largely affected when the coal-seam is inclined. The downhill spoiling mode should be applied wherever possible. The DNS pattern allows wider pit width intervals as well as longer sets and longer reaches.